MECHANISM STUDY OF MADEIRA VEIN (Anredera cordifolia (Ten.) v. Steenis) LEAVES EXTRACT AS ANTIHYPERLIPIDEMIA AND IN SILICO STUDY OF ITS ACTIVE COMPOUND TO HMG CO-A REDUCTASE - LESTARI (NIM : 30713003), DWINTHA
Hyperlipidemia is a disorder of lipoprotein metabolism resulting changes in one or more lipid components included total cholesterol, triglyceride and LDL levels increase, and HDL level decrease in the blood. Hyperlipidemia is a risk factor for endothelial damage which will lead to atherosclerosis and can lead to coronary heart disease. The death rate of coronary heart disease has always increased every year. Therapies for hyperlipidemia be developed as a complication of coronary heart disease due to hyperlipidemia still the leading cause of death. Madeira vein was known had antihyperlipidemic effect both empirical and preclinically. But it still need further research to determine the mechanism of binahong as antihyperlipidemic agent. This study aims to examine the antihyperlipidemia effect of binahong leaves, determine the mechanism of extract and its fractions in decreasing lipid levels on rat aortic endothelial by microscopic, inhibitory of lipid peroxidation and antioxidant. Furthermore was performed study of binahong leaves subfraction to HMG Co-A reductase inhibition, decreasing in rat aortic endothelial by microscopic and blood lipid levels. Then active compound of subfraction was tested to inhibit HMG Co-A reductase enzyme activity by in silico. In vivo studies were conducted to examine the effects of extract, fraction and subfraction of madeira vein leaves as antihyperlipidemic agent. Rats were given by high cholesterol feed for three months, then lipoprotein profiles and aortic endothelial were observed. In vitro studies were carried out for testing antioxidant activity of extract and fractions by measuring decrease in absorbance of free radical DPPH, and activity of madeira vein leaves subfraction to inhibit HMG Co-A reductase enzyme. Ex vivo studies were performed to test lipid antiperoxidation activity of extract and binahong fractions. In silico study of active compound in subfraction to inhibit HMG Co-A reductase enzyme was determined by predicting apigenin and apigetrin binding as ligands. The in vivo test results showed that ethanol extract (50 mg/kg bw, 100 mg/kg bw, 200 mg/kg bw), ethyl acetate fraction (5.9 mg/kg bw, 11.8 mg/kg bw, 23.6 mg/kg bw) and subfraction (0.24 mg/kg bw and 0.12 mg/kg bw) had influence in lipoprotein profile significantly different from the control group (p<0.05 and exposed improvement of endothelial cells after administration of extract, fraction and subfraction of madeira vein leaves for 3 weeks. The ethanol extract of the binahong leaves 200 mg/kg bw and ethyl acetate fraction 23.6 mg/kg bw improved lipoprotein profile and repaired endothelial damage which were equivalent to simvastatin (3,6 mg/kg bw). Madeira vein subfraction with dose of 0,24 mg/kg bw showed good results in lipoprotein profile and repaired endothelial damage. The ex vivo lipid peroxidation test results presented the percentage of lipid peroxidation inhibition which was measured by uv-visible spectrophotometry at ? 532 nm, and compared with simvastatin. The percentage of lipid peroxidation inhibition of ethanol extract of madeira vein leaves with doses 50 mg/kg bw, 100 mg/kg bw and 200 mg/kg bw were 56.7%, 65.2%, 68.7%, respectively. The ethyl acetate fraction (dose 5.9 mg/kg bw, dose 11.8 mg/kg bw and dose 23.6 mg/kg bw) gave lipid peroxidation inhibition of 65.9%, 69.4%, 72.9% respectively, greater than the n-hexane fraction and water fraction. In vitro antioxidant test revealed that IC50 DPPH value of ethyl acetate fraction was lower than the other fractions. Thin layer chromatogram demonstrated that the binahong leaves subfraction contained apigenin and apigetrin. IC50 subfraction (1,12 µg/mL) in inhibiting HMG Co-A reductase was similar to IC50 apigenin (1,25 µg/mL). It demonstrated that apigenin was major contributor in subfraction of madeira vein to inhibit HMG CoA reductase. The results of in silico test expressed that apigenin and apigetrin had affinity to bind to the active side of the HMG Co-A reductase enzyme. Apigenin had more negative bond-free energy (-7 kcal/mol) than apigetrin (- 5.9 kcal/mol) which showed apigenin had greater ability to inhibit HMG Co-A reductase enzyme than apigetrin. Based on result it can be concluded that extract, fraction and subfraction of madeira vein leaves had antihyperlipidemia effect which exposed by lipoprotein profile improvement and lipid reduction in endothelial cells, also the binahong leaves subfraction showed inhibitory activity to HMG Co-A reductase. Apigenin was active compound in madeira vein leaves active subfraction. Apigenin and apigetrin had affinity to inhibit HMG Co-A reductase in silico, and apigenin had larger affinity than apigetrin.